Penerapan E-Modul Interaktif untuk Meningkatkan Hasil Belajar Peserta Didik - Nur Aulia Fadhillah; Salma Samputri; Sitti Saenab (Celebes Science Education, 2025)
This study aims to determine 1) How high is the increase in learning outcomes of VII grade students of SMP Negeri 2 Sungguminasa after being taught with Interactive E-Modules, 2) Knowing whether there is a difference in the average N-Gain score of learning outcomes of students in class VII SMP Negeri 2 Sungguminasa. This type of research is Pre-Experimental research with a research design using One Group Pretest-Posttest Design. The population was all students of class VII of SMPN 2 Sungguminasa in the 2022/2023 academic year consisting of 11 classes with a total of 354 people, the sample was selected by purposive sampling, with 1 class, namely class VII.10 totaling 31 people as an experimental class. The research instrument was in the form of learning outcomes test questions. Data were analyzed with descriptive statistics and inferential statistics. Based on the results of the study, it is concluded that there is a difference in the average score of learning outcomes of students in class VII SMP Negeri 2 Sungguminasa with the application of Interactive E-Modules.